Selection of thermotolerant Corynebacterium glutamicum strains for organic acid biosynthesis - Leszczewicz, Martyna (Array, 2019)
In recent years, Corynebacterium glutamicum has been considered as producer of many valuable chemical compounds. Among them, organic acids such as L-lactic and succinic acids are the most important ones. It is known that the wild-type C. glutamicum grows well in the temperature range between 25 and 37 °C. Above 40 °C, the biomass growth usually abruptly stops; however, the bacteria remain metabolically active. High temperature affects the metabolic activity of C. glutamicum cells and can lead to changes in the composition and quantity of the fermentation products. Therefore, in a series of subsequent selection steps, we tried to obtain prototrophic strains capable of growing at 44 °C from the culture of homoserine auxotroph C. glutamicum ATCC 13287. During selection, we used complex and mineral media containing succinic and citric acids. As a result, we obtained 47 clones able to grow at elevated temperature. Moreover, the estimated optimal growth temperature for several of them was about 40 °C or higher. Under oxygen limitation conditions, C. glutamicum strains produce organic acids. Regardless of the tested clone, L-lactic acid was the main product. However, its concentration was the highest in the cultures performed at 44 °C. The elevated temperature also affected the biosynthesis of other organic acids. Compared to the parental strain, the concentration of acetic acid increased, and of succinic acid decreased in the cultures of thermotolerant strains. Strain RCG44.3 exhibited interesting properties; it was able to synthesise 27.1 g/L L-lactic acid, with production yield of 0.57 g/g, during 24 h of fermentation at 44 °C.